Reflexión pedagógica: crisis y razón de la práctica docente como ejercicio crítico - María Jesús Vitón de Antonio (Escola Superior de Educação de Paula Frassinetti, 2012)
Forcing us to take a deeper look, through critical reflection, at the different faces of the crisis and of education gives us the opportunity, at this momento, to try to get answers to who that presents himself as a teacher, not so much from one more question, but from the fundamental question which is the link and responsibility between what is done in the classroom and the way that practice helps achieve the purpose of a qualified democratic education. In this sense, we can ask: is there an education in times of crisis, which is different from what is institutionalized in other periods? or, in other words, what is the purpose of is education in times of crisis?